Englicious: Teaching English Grammar in Schools. (2nd November 2015) - Fletcher, Rachel
Abstract : Englicious is a new online library of resources for English language teachers that has been designed by the Survey of English Usage at UCL. It offers not only lesson plans and activities for use in the classroom, but a collection of Continuing Professional Development resources for teachers, all aimed at supporting the teaching of the new National Curriculum in England. There is a particular focus on spelling, punctuation and grammar (SPaG), and especially on preparing pupils for the Year 3 and Year 6 SPaG tests, but users will also find materials covering many other aspects of English Language at both a primary and a secondary level.